Cloaking antibodies are prevalent in Burkholderia cepacia complex infection and their removal restores serum killing - Pham, Amy; Tan, Kellynn K. Y.; Ledger, Emma L.; Smith, Daniel J.; Reid, David W.; Burr, Lucy; Chambers, Daniel C.; Wells, Timothy J. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe Burkholderia cepacia complex encompasses a group of gram-negative opportunistic pathogens that cause chronic lung infections in people with cystic fibrosis. Distinct from other respiratory pathogens, Burkholderia causes a unique clinical disease in a subset of patients known as ‘cepacia syndrome’, fulminant pneumonia accompanied by bacteraemia and sepsis with a mortality rate of up to 75%. Due to the bacteraemia associated with this disease, the mechanisms that allow Burkholderia to resist the bactericidal effects of serum complement-depending killing are vital. Antibodies usually promote serum killing; however, we have described ‘cloaking antibodies’, specific for lipopolysaccharides that paradoxically protect serum-sensitive bacteria from complement-mediated lysis. Cloaking antibodies that protect Pseudomonas aeruginosa have been found in 24%–41% of patients with chronic lung diseases. The presence of these antibodies is also associated with worse clinical outcomes. Here, we sought to determine the relevance of cloaking antibodies in patients with Burkholderia infection.MethodsTwelve Burkholderia spp. were isolated from nine pwCF and characterised for susceptibility to healthy control serum. Patient serum was analysed for the titre of the cloaking antibody. The ability of the patient serum to prevent healthy control serum (HCS) killing of its cognate isolates was determined.ResultsWe found that several of the Burkholderia strains were shared between patients. Ten of the 12 isolates were highly susceptible to HCS killing. Four of nine (44%) patients had cloaking antibodies that protected their cognate strain from serum killing. Depleting cloaking antibodies from patient serum restored HCS killing of Burkholderia isolates.DiscussionCloaking antibodies are prevalent in patients with Burkholderia pulmonary infection and protect these strains from serum killing. Removal of cloaking antibodies via plasmapheresis, as previously described for individuals with life-threatening Pseudomonas infection, may be a useful new strategy for those with serious and life-threatening Burkholderia infection.